2022
DOI: 10.1007/s12020-022-03232-3
|View full text |Cite
|
Sign up to set email alerts
|

Filling the gap between the heart and the body in acromegaly: a case-control study

Abstract: Objective Cardiovascul diseases are the most common comorbidities in acromegaly. Potential parameters in pathology of cardiovascular comorbidities are changes in levels of growth hormone (GH) and insulin-like growth factor 1 (IGF-1) as well as body composition parameters. Purpose The aim of this study was to examine morphological and functional parameters of the cardiovascular system by echocardiography and to assess its relationship with disease activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In an animal study, 6 out of 11 cats with acromegaly showed enlarged LA [22]. Human studies confirmed the dilation of LA in acromegaly patients with and without heart failure [1,6,7,23,28,30]. LA volume index was higher in acromegaly patients [30].…”
Section: In Acromegalymentioning
confidence: 84%
See 1 more Smart Citation
“…In an animal study, 6 out of 11 cats with acromegaly showed enlarged LA [22]. Human studies confirmed the dilation of LA in acromegaly patients with and without heart failure [1,6,7,23,28,30]. LA volume index was higher in acromegaly patients [30].…”
Section: In Acromegalymentioning
confidence: 84%
“…However, cardiac fibrosis was absent in all patients, irrespective of the estimated duration of the disease [27]. In a recent study, the prevalence of LV hypertrophy in acromegaly patients was 67% (78% concentric, 22% eccentric) [28].…”
Section: In Acromegaly LV Structure Volumes and Hypertrophymentioning
confidence: 87%
“…[18]Also, AP-LAD, IVST, LVPWD, and LVMi were higher in acromegaly patients. [3,22] In this study, the percentage of LVMi abnormalities was calculated to be 12.1% and 9.9% in patients with pediatricand adult-onset, while the common echocardiographic abnormalities included valvular regurgitation [23], left atrial enlargement, and enlarged LVEDD. Previously reported abnormalities of cardiac structure in patients with acromegaly mainly focused on ventricular hypertrophy, and descriptions of ventricular enlargement were uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation could be explained by the amount of different tissues in the trunk, as the amount of lean trunk mass on average doubles that of the average trunk fat mass ( 59 ). In active acromegaly, acceleration effect of excess GH/IGF-I on anabolism results in additional increase in lean mass, including in trunk ( 60 ). Another cause could be the artefactual effect of the regional presence of the soft tissue on the DXA scan, which could affect TBS values.…”
Section: Discussionmentioning
confidence: 99%